1984
DOI: 10.1002/j.1460-2075.1984.tb01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a class C transcription factor which forms a stable complex with tRNA genes.

Abstract: A yeast extract was fractionated to resolve the factors involved in the transcription of yeast tRNA genes. An in vitro transcription system was reconstituted with two separate protein fractions and purified RNA polymerase C (III). Optimal conditions for tRNA synthesis have been determined. One essential component, termed tau factor, was partially purified by conventional chromatographic methods on heparin‐agarose and DEAE‐Sephadex; it sedimented as a large macromolecule in glycerol gradients (mol. wt. approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 33 publications
3
70
1
Order By: Relevance
“…Assays were performed as described previously (24) using purified protein extracts obtained from heparin-Sepharose chromatography (25). Proteins were extracted from yeast strain BWG1-7A, purified, and incubated with 40-base pair DNA fragments harboring the glycine regulatory region of GCV2.…”
Section: Gel Mobility Shift Assaymentioning
confidence: 99%
“…Assays were performed as described previously (24) using purified protein extracts obtained from heparin-Sepharose chromatography (25). Proteins were extracted from yeast strain BWG1-7A, purified, and incubated with 40-base pair DNA fragments harboring the glycine regulatory region of GCV2.…”
Section: Gel Mobility Shift Assaymentioning
confidence: 99%
“…The TFIIIB factor was partially purified on a heparin-ultrogel (Pharmacia) column from cells expressing the wild type or a modified copy of PCF4 as described (31,32). Heparin-ultrogel fractions containing TFIIIB activity were pooled and used for affinity purification (see Figure 2).…”
Section: Tfiib' Fractionationmentioning
confidence: 99%
“…The selective recognition of the tRNA genes by this ©IRL Press machinery rests on the presence of two conserved intragenic sequence elements, the A and B blocks, which correspond to the invariant bases of the D and TICG loops of tRNAs (Ciliberto et al, 1983;Geiduschek and Tocchini-Valentini, 1988). As a primary step of gene activation, the promoting sequences are recognized by transcription factor TFIHC, or T in the yeast system, in the absence of any other transcriptional component (Lassar et al, 1983;Ruet et al, 1984). Factor TFIIIB contributes to the stability of TFIIIC -DNA complexes and is required for transcription complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…It does not bind to DNA by itself (Klekamp and Weil, 1986;Waldschmidt et al, 1988). Yeast factor r and its interaction with tDNA have been extensively studied (Klementz et al, 1982;Ruet et al, 1984). Nuclease protection and methylation experiments (Camier et al, 1985;Stillman et al, 1985a), as well as point mutation analyses (Baker and Hall, 1984;Baker et al, 1986), have demonstrated the specific binding of r to the A and B blocks, the involvement of critical bases and the prominent role of the B block sequence in complex formation.…”
Section: Introductionmentioning
confidence: 99%